(untitled) (Journal of Shaheed Suhrawardy Medical College, 2021)
Introduction: Tibia fractures are the most common long bone fractures encountered by the orthopedic surgeons and distal tibia fractures have the second highest incidence of all tibia fractures after the middle third of tibia the distal tibial fractures are unique and are considered as most challenging fractures to treat due to its proximity to the ankle joint and its superficial nature. The objective of this study is to compare two osteosynthesis systems developed for surgical treatment of distal tibia fractures: the intramedullary nailing and the MIPO technique. Methods: The study was conducted between Jan 2018 to Dec 2019. 30 patients with extraarticular distal tibia fracture treated with intramedullary nailing and MIPO technique were reviewed retrospectively and clinical outcome was evaluated according to American Orthopaedic Foot and Ankle Score. Results: 15 patients were treated with intramedullary nail and 15 with MIPO technique. Fibular fixation was done in cases where fibular fracture was at or below the level of tibial fractures. We found no difference in terms of time for fracture union, mal-union, non-union, duration of surgery and amount of blood loss. But there was significant difference in terms of infection and duration of hospital stay. Also weight bearing was possible much earlier in intramedullary group as compared to the MIPO group. Conclusion: Thus we conclude that intramedullary nailing is better choice of implant in patients with extra- articular distal tibia fractures and helps in early weight bearing and ambulation of patient with fewer complications. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 33-37